Qualitative and Quantitative Analysis of Phytochemicals in Sayeok-Tang via UPLC-Q-Orbitrap-MS and UPLC-TQ-MS/MS - Yu Jin Kim; Seol Jang; Youn-Hwan Hwang (Pharmaceuticals, 2024)
Sayeok-tang (SYT) is a traditional herbal formula comprising three medicinal herbs: Glycyrrhiza uralensis, Zingiber officinale, and Aconitum carmichaeli. Several studies have employed liquid chromatography-mass spectrometry (LC-MS) to qualitatively analyze the components and metabolites of SYT in vitro and in vivo; however, studies on quantitative analysis of SYT, which is important for quality control, are absent or limited to only a few components. In this study, ultrahigh-performance liquid chromatography coupled with quadrupole (UPLC-Q)-Orbitrap-MS was used to screen the phytochemicals of SYT, revealing a total of 42 compounds. Among them, 24 compounds were simultaneously quantified within 20 min via UPLC-TQ-MS/MS in the multiple reaction monitoring mode. The developed analytical method was validated for its linearity (r2 ≥ 0.9992), precision (0.36–2.96%), accuracy (−6.52–4.64%), and recovery (94.39–119.07%) for all analytes, exhibiting acceptable results. The validated method was applied in the analysis of SYT extracts, and the 24 compounds were quantified in the range of 0.004–6.882 mg/g (CV ≤ 3.746%). Among them, liquiritin apioside (6.870–6.933 mg/g), glycyrrhizic acid (5.418–5.540 mg/g), and liquiritin (1.303–1.331 mg/g) from G. uralensis were identified as the relatively abundant compounds. The presented validated analytical method is highly promising for the comprehensive quality control of SYT, offering fast, highly sensitive, and reliable analysis.